Positive Affect Predicts Turnover Intention Mediated by Online Work Engagement: A Perspective of R&D Professionals in the Information and Communication Technology Industry - Hong, Jon-Chao; Petsangsri, Sirirat; Cui, Yuting (Frontiers in Psychology, 2021)
Remote work has become the most popular approach during the COVID-19 lockdown; however, remote work engagement is an issue which creates challenges for human resource management. Some individuals engage in work no matter how difficult the job is, but some people’s minds wander, no matter how simple the job is. To address this issue, this study drew on trait activation theory, which indicates that one’s positive disposition may affect one’s turnover intention mediated by work engagement, to formulate a research model to test the associations between R&D professionals’ positive affect and their perception of work engagement to their subsequent turnover intention. Questionnaires were distributed to R&D professionals working in China information technology through some Instant Message groups. In total, 386 valid questionnaires were collected. After item and construct reliability and validity testing, this study adopted confirmatory factor analysis with structural equation modeling to verify the research model. The study found that the level of positive affect, remote work engagement and turnover intention of R&D personnel in the IT industry were high. The positive affect of R&D personnel can positively predict three types of remote work engagement, and all three types of remote work engagement of R&D personnel can negatively predict their turnover intention. The results suggest that if human resource managers working in the science and technology industry want to reduce the turnover rate of R&D workers under pressure from COVID-19, they should enhance workers’ remote engagement by selecting R&D workers with a high level of positive affect.